PENILAIAN MIKROBIOLOGIS MENGGUNAKAN METODE TPC DAN MPN SERTA EVALUASI ORAGANOLEPTIK DI OBJEK WISATA ALAM SUMBER GENTONG DESA TIRTOMOYO KABUPATEN MALANG - Susanto, Misbahuddin Febrian; Faisal; Syauqi, Ahmad (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Waterr irs oner of ther materrirals or erlermernts that maker up ther erarth that allows lirfer to taker placer as irt irs on erarth. Waterr irs userd to merert ther nererds of human lirfer. Oner of ther sourcers of sprirng waterr irn Malang Cirty comers from ther natural tourirsm of ther barrerl sourcer locaterd irn Manglirawan Virllager, Malang Rergerncy. Rerserarch was carrirerd out on ther sprirng waterr sourcer wirth ther airm of obtairnirng mircrobirologircal terst rersults baserd on TPC, MPN and organolerptirc asserssmernt merthods. Thirs study users a quantirtatirver derscrirptirver merthod that airmsir to derscrirber and merasurer cerrtairn varirablers wirthout manirpulatirng therm whirch airms to irprovirder a dertairlerd and accurater pircturer of th er characterrirstircs or condirtirons obserrverd. Ther rersults of ther TPC terst of waterr samplers that haver not berern affercterd by human actirvirty werrer obtairnerd from ther averrager calculatiron of total bacterrira as much as 3.1 x 103 CFU /ml, whirler irn samplers that haver berern affercterd by human actirvirtirers, ther averrager calculatiron of total bacterrira was obtairnerd as much as 1.2 x 104 CFU /ml. MPN terst usirng ErMB merdira Irn orderr to firnd bacterriral colonirers, irncludirng Erscherrirchira colir (Non-fercal), Klerbsirerlla sp and Ernterrobacterr sp. Irn ther Organolerptirc Asserssmernt wirth addirtironal paramerterrs, ther rersults werrer obtairnerd that sampler A was qualirfirerd as cleran waterr suirtabler for consumptiron whirler sampler B dird not merert ther rerquirrermernts. Bercauser ther MPN terst found Erscherrirchira colir / Colirform, irt can ber concluderd that samplers A and B arer not erlirgirbler as waterr that can ber consumerd dirrerctly accordirng to ther Rergulatiron of ther Mirnirsterr of Heralth No. 492 /MErNKErS /PErR/IrV /2010 . H owerverr, irbaserd on ther addirtiron of Statuter Book of ther Rerpublirc of Irndonersira Numberr 4161 irn ther irattachmernt to gov errnmernt irrergulatiron No. 82 of 2001 artircler 8 paragraph 1, sampler A, whirch irs ther placer wherrer ther waterr comers out, can ber ir userd as a sourcer of drirnkirng waterr on ther condirtironir that irt must go through ther treratmernt procerss firrst